2020
DOI: 10.1103/physrevc.101.011301
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the heaviest elements: K isomer in No250

Abstract: Decay spectroscopy of 250 No has been performed using digital electronics and pulse-shape analysis of the fast nuclear decays for the first time. Previous studies of 250 No reported two distinct fission decay lifetimes, related to the direct fission of the ground state and to the decay of an isomeric state but without the possibility to determine if the isomeric state decayed directly via fission or via internal electromagnetic transitions to the ground state. The data obtained in the current experiment allowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The achieved results could not provide a clear answer to whether the long-lived activity of 250 No is caused by direct SF from the K-isomeric state or by delayed fission of the ground state after electromagnetic transitions. It can be concluded that the analysis of the prompt neutron multiplicity distribution does not allow us to confidently answer the question as expected from the results of [9]. The average number of neutrons per SF of 250 No was determined to be .…”
Section: P(a|θ) P(b|θ)mentioning
confidence: 84%
See 2 more Smart Citations
“…The achieved results could not provide a clear answer to whether the long-lived activity of 250 No is caused by direct SF from the K-isomeric state or by delayed fission of the ground state after electromagnetic transitions. It can be concluded that the analysis of the prompt neutron multiplicity distribution does not allow us to confidently answer the question as expected from the results of [9]. The average number of neutrons per SF of 250 No was determined to be .…”
Section: P(a|θ) P(b|θ)mentioning
confidence: 84%
“…Later, using the mass analyzer FMA [8], it was confirmed that both activities belonged to 250 No. An interesting result was then reported in [9], in which the average multiplicities of prompt neutron emission in the SF corresponding to each activity were measured for the first time. The difference between the average number of neutrons per SF for the short-and long-lived states was found to be large (4.38 0.13 and 3.9 0.2) but still statistically insignificant (the difference…”
Section: Introduction Z > 100mentioning
confidence: 88%
See 1 more Smart Citation
“…The advantages of CANDI-type systems for the solution of various physics and measurement technical issues and for superheavy element search experiments are demonstrated in Refs. [11][12][13]16,41,[43][44][45][46].…”
Section: Experimental Setup and Conditionsmentioning
confidence: 99%
“…More commonly, however, the metastable states are used to gain information on nuclear structure; if one measures the energy, rate, and multipole of the transition depopulating the level, an access is gained to the underlying transition matrix element. Furthermore, the decay of the isomeric state might populate otherwise inaccessible intermediate state(s) that in turn can be studied, for example, on a focal plane of a recoil separator [8,9], or said transitions can be used to gain high selectivity in the form of a recoil-isomer decay tagging [10][11][12].…”
Section: Introductionmentioning
confidence: 99%